Trypanosomiasis-induced Th17-like immune responses in carp. - Carla M S Ribeiro; Maria J S L Pontes; Steve Bird; Magdalena Chadzinska; Marleen Scheer; B M Lidy Verburg-van Kemenade; Huub F J Savelkoul; Geert F Wiegertjes (PLoS ONE, 2010)
BACKGROUND: In mammalian vertebrates, the cytokine interleukin (IL)-12 consists of a heterodimer between p35 and p40 subunits whereas interleukin-23 is formed by a heterodimer between p19 and p40 subunits. During an immune response, the balance between IL-12 and IL-23 can depend on the nature of the pathogen associated molecular pattern (PAMP) recognized by, for example TLR2, leading to a preferential production of IL-23. IL-23 production promotes a Th17-mediated immune response characterized by the production of IL-17A/F and several chemokines, important for neutrophil recruitment and activation. For the cold blooded vertebrate common carp, only the IL-12 subunits have been described so far. METHODOLOGY/PRINCIPAL FINDINGS: Common carp is the natural host of two protozoan parasites: Trypanoplasma borreli and Trypanosoma carassii. We found that these parasites negatively affect p35 and p40a gene expression in carp. Transfection studies of HEK293 and carp macrophages show that T. carassii-derived PAMPs are agonists of carp TLR2, promoting p19 and p40c gene expression. The two protozoan parasites induce different immune responses as assessed by gene expression and histological studies. During T. carassii infections, in particular, we observed a propensity to induce p19 and p40c gene expression, suggestive of the formation of IL-23. Infections with T. borreli and T. carassii lead to an increase of IFN-γ2 gene expression whereas IL-17A/F2 gene expression was only observed during T. carasssii infections. The moderate increase in the number of splenic macrophages during T. borreli infection contrasts the marked increase in the number of splenic neutrophilic granulocytes during T. carassii infection, along with an increased gene expression of metalloproteinase-9 and chemokines. CONCLUSION/SIGNIFICANCE: This is the first study that provides evidence for a Th17-like immune response in fish in response to infection with a protozoan parasite.